Pengaruh Work-Life Balance terhadap Produktivitas dan Loyalitas Pegawai Kantor Walikota Pekanbaru - Nizamil Fadhli; Israwati; Zulham Mahendra (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to analyze the influence of work-life balance on the productivity and loyalty of employees in the Pekanbaru City Government. In the modern era with increasingly complex work demands, understanding work-life balance has become crucial in governmental human resource management. Employing a quantitative approach, this research involved 100 respondents from the Pekanbaru City Government. Data were collected through a questionnaire using a 5-point Likert scale, measuring perceptions of work-life balance, productivity, and employee loyalty. Data analysis included descriptive statistics, classical assumption tests, correlation analysis, and multiple linear regression. The results show that work-life balance has a significant positive effect on both productivity (β = 0.688, p < 0.001) and employee loyalty (β = 0.688, p < 0.001). Work-life balance explains 52.4% of the variance in employee productivity and loyalty (R² = 0.524). A very strong correlation was also found between productivity and employee loyalty (r = 1.000, p < 0.01). The levels of work-life balance (M = 4.37, SD = 0.92), productivity (M = 4.51, SD = 0.78), and employee loyalty (M = 4.51, SD = 0.78) were generally quite high. This study concludes that work-life balance is a key factor in improving productivity and loyalty of local government employees. Practical implications include the importance of developing policies and programs that support work-life balance to enhance organizational performance and the quality of public services.